ANALISIS STRATEGI KEBIJAKAN LUAR NEGERI INDONESIA DALAM BELT AND ROAD INITIATIVE - Riza Iskandar; Ambarwati Ambarwati; Muhammed Irwiyana Tri Putra (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2022)
This study aims to analyze Indonesia's foreign policy strategy during 2014-2019 toward the Belt and Road Initiative (BRI) initiated by China’s Xi Jinping. The study focuses on how Indonesia defends its national interests, that is to become the Global Maritime Fulcrume (PMD). Under the administration of President Joko Widodo, PMD's vision has been translated into efforts to build infrastructure and enforce the law in Indonesian waters, one of which is to eradicate illegal fishing. The results of the study found that the policy triggered positive and negative responses from China. Regarding the opportunity to invest in Indonesia's infrastructure development, China responded enthusiastically. However, in the context of eradicating its state-owned fishing vessels, China has tried to use various means, including using its investment as an instrument to influence Indonesian policies.